Genocide and resistance Nr. 9(1) - Ivanovas, Bernaras; Maslauskienė , Nijolė; Bubnys, Arūnas; Jonušauskas, Laurynas; Tininis, Vytautas; Truska, Liudas; Kasperavičius, Algis; Žiūkas, Mindaugas (Genocidas ir rezistencija, 2001)
Full Issue (paper copy scan)